Hammock: A Maritime Tool - Panico, Michele (East Carolina University, 2018)
During the age of sail, sailors slept in hammocks made of canvas, suspended on the gundecks and secured to the beams above. This work seeks to understand the adoption and adaptation of hammocks as a maritime tool on sailing vessels and the subsequent impact and changes their presence caused. The adoption of hammocks onto maritime vessels affected all aspects of life at sea; including alterations to the construction and supplies needed aboard ships, which resulted in monetary impacts. Hammocks allowed for an increase in the number of men aboard vessels, they shaped modifications and improvements in sleeping conditions, and strengthened the divisions in ranks, while also acting as a means of comradery. In addition, hammocks created revisions in rules and regulations. Likewise, they altered forms of protection and defenses. Furthermore, hammocks affected health and hygiene by playing large roles in governing the cleanliness of ships and sailors. They also had various functions in relation to the sickbay, including a key part in burial. Finally, this thesis concludes with the replacement of hammocks by bunks. Ultimately, it evaluates the hammock as a maritime tool that influenced life at sea during the age of sail.
Keywords: Maritime; Navy; Naval Ship; Hammocks--History; Seafaring life--History; Naval hygiene